ANALISIS KINERJA PENGURUS TERHADAP EFEKTIVITAS PELAKSANAAN PROGRAM KERJA ORGANISASI - Yolanda, Rika; Emeliya, Risyda; Khairina, Ghina (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the performance of the management on the effectiveness of the implementation of a work program. This study uses literature studies which are efforts that can be made by the author to obtain various data sourced from previous research, journals, scientific books, and so on in accordance with the problem being studied. There are indicators of effectiveness, which can be determined from: Time permanence, cost calculation, measurement, making choices, and accuracy in thinking